Post-crisis Political Normalisation? The 2018 Presidential Elections in the Republic of Cyprus - Triga, Vasiliki; Mendez, Fernando; Djouvas, Constantinos (My University, 2019)
This article takes stock of the most recent presidential election in the Republic of Cyprus and connects it to broader currents in post-crisis European political settings. Although the elections took place against a backdrop of improving economic prospects, the crisis has left its political mark in a number of areas we identify that include a growing political fragmentation, the rise of the far right and increased voter abstention. The empirical analysis focuses on the media campaign and draws on a topic-modelling approach to identify and contrast emphasis given to policy issues over the two electoral rounds. The policy themes identified clustered around two dominant dimensions of political conflict: the Cyprus conflict and the economy.
Keywords: Abstention; Cyprus problem; Economic crisis; ELAM; Great Recession; Polarisation; Topic modelling